Proses Pembentukan Kabupaten Pulau Morotai Dalam Rangka Pelaksanaan Pemerintahan Daerah - AZIZ, McBILL ABDUL (2012)
This research aims to fine the process of formation of Morotai Island country, symptoms and element that prouce the idea offorming the ditrect Morotai Island. After learning several causes, the research will lay the processes that have been passed in the formation of the district Morotai and then placed on the theoretical and juridical aspect. In this research note background of Morotai Island formation starts from people'sdesire to run a community-based development in order to impruve the welfare ofher life. This is supported by the existence of natural resources Morotai Island Regency is very rich and balanced by the increasing capacity human resource for thr more advanced public education in thr distict of the island of Morotai. On the other hand the desire to get a juridical basis the establisment of statute No. 32 of 2004 0n local government. The process of formation of Morotai Island Distrct has been in accordance with Statute No 32 Year 2004 on local government as a juridical foundation. In this law set the formation of district with due consideration to economic, regional potential, social, cultural, social political, population, area and other considerations that enable the implementation of regional autonomy.